Language Choice In Multilingual Society A Sociolinguistic Study Of Tanjung Luar Community - Herlina Kusuma Ningrat (Tarbawi, 2019)
This study deals with language choice in Tanjung Luar Community. It is aimed at identifying the domain of usage of the languages and factors affecting the language choice. Sampling technique used in this study is Proportional Cluster Sample wherein the population is divided into groups. The population of this study was the whole inhabitants of Tanjung Luar Community. The data on this study was collected by observing, giving questionnaire and slightly interviewing. Then, the data was analyzed by doing several steps namely identifying languages used in Tanjung Luar Community, classifying language choice based on the domains, describing factors for language choice, and explaining the comparison between the finding of this study and the previous theories. The result of this study shows various languages and the domains of usage wherein at home, as well at informal domain and at same-ethnic domain, the people dominantly use Bajo Language. However, at formal domain, the people tend to use Bahasa Indonesia dominantly. The study also found two majors factors affecting language choice namely internal factors including language attitude, message or purpose and acknowledgment; as well as external factors including interlocutor, topic, domain, and social status.